Analisis Pengelolaan Limbah Medis Program Imunisasi Rutin Di Puskesmas Kota Manado - Alam, Syamsu; Katiandagho, Dismo; Pinontoan, Sabrina P. M. (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Medical waste management is an important aspect of maintaining environmental health, especially in healthcare facilities such as community health centers (Puskesmas). Poorly managed medical waste can become a source of disease transmission and environmental contamination. This study aims to analyze the medical waste management system of the immunization program in 16 Puskesmas in Manado City, focusing on the behavior of personnel, available facilities, knowledge of staff, as well as the processes of transportation, storage, and disposal of medical waste. The results indicate that 100% of Puskesmas have met the standards regarding the behavior of immunization staff, available facilities, and staff knowledge. However, there are discrepancies in the waste transportation process in 31.2% of Puskesmas, indicating delays in waste transportation of more than one week, and even up to 18 months in some locations. Budget limitations and transportation contracts are the main obstacles in waste management. The waste storage in 68.8% of Puskesmas is in accordance with the standards set by the Minister of Health Regulation (Permenkes) 2019, which requires waste to be stored for a maximum of one week or in cold storage for up to 90 days  Keywords: Immunizatiom Polution, Waste Management, Community Health Cantres